Kinesio Taping Associated with Acupuncture in the Treatment of the Paretic Upper Limb After Stroke - Moisés S. Dall'Agnol; Fernanda Cechetti (Medical Association of Pharmacopuncture Institute, 2018)
The leading cause of disability in adults, leads to different consequences, such as hemiparesis and loss of function in the upper limb which can impair the performance of activities of daily living. Different techniques, such as like acupuncture and Kinesio Taping (KT), have been used to ameliorate this condition. However, there is no consensus on their concomitant effect on neurological patients. This study aimed to analyze the effects of acupuncture associated with KT on the upper limb of patients with chronic hemiparesis after stroke. In this clinical study, 16 subjects were divided into two intervention groups: acupuncture (ACP)-12 sessions of acupuncture-and acupuncture + Kinesio Taping (ACP-KT)-12 sessions of acupuncture plus KT. The Modified Ashworth Scale (spasticity), active goniometry [range of motion (ROM)], and the Wolf Motor Function Test (speed of movement) were used to assess the function of the affected upper limb. As a main result, both groups reduced spasticity in some studied musculature and increased ROM (p < 0.05), without intergroup difference. Moreover, there was no significant improvement concerning speed of movement in either group. Acupuncture was effective in reducing spasticity and increasing ROM of paretic upper limb after stroke, but did not contribute significantly to speed and quality of movement. KT did not show significant benefits concerning the analyzed variables. Keywords: acupuncture, athletic tape, muscle spasticity, stroke